Photoinduced flexible graphene/polymer nanocomposites: Design, formation mechanism, and properties engineering; Carbon; Vol. 194 - Lipovka A. A. Anna Anatolyevna; Petrov I. S. Iljya Sergeevich; Fatkullin M. I. Maksim Ilgizovich; Murastov G. V. Gennadiy Viktorovich; Ivanov A. A. Aleksey Alekseevich; Villa Pineda N. E. Nelson Enrrique; Shchadenko S. V. Sergey Vladimirovich; Averkiev A. A. Andrey Alekseevich; Chernova A. P. Anna Pavlovna; Gubarev F. A. Fedor Aleksandrovich; Saqib M. Muhammad; Sheng W. Wenbo; et al. (2022, 2022)
Title screen